2021
DOI: 10.4314/ejhs.v31i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concept Mapping Education on Critical Thinking Skills of Medical Students: A Quasi-experimental Study

Abstract: BACKGROUND፡ Fostering critical thinking (CT) is one of the most important missions in medical education. Concept mapping is a method used to plan and create medical care through a diagrammatic representation of patient problems and medical interventions. Concept mapping as a general method can be used to improve CT skills in medical students. The aim of this study was to explore the effect of concept mapping on CT skills of medical students.METHODS: This quasi-experimental study was conducted on 100 second-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The evaluation of learning score showed that this criteria was increased after intervention in both groups. This result is in agreement with Islami et al [ 23 ]. Rigi et al Showed that the clinical skill of preeclampsia control in both the concept map training and the traditional method groups after two weeks of the intervention significantly increased compared to before the intervention [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…The evaluation of learning score showed that this criteria was increased after intervention in both groups. This result is in agreement with Islami et al [ 23 ]. Rigi et al Showed that the clinical skill of preeclampsia control in both the concept map training and the traditional method groups after two weeks of the intervention significantly increased compared to before the intervention [ 24 ].…”
Section: Discussionsupporting
confidence: 94%
“…The previous studies measured the effect of SC-Mapping on the students' HOT based on their performance in accomplishing the assessment before (pre-test) and after learning (post-test) [10], [12]. For example, [12] provided a test consisting of 12 questions categorized as applying, analyzing, evaluating, and creating to investigate the students' HOT comprehension before and after concept mapping was conducted in the laboratory activities.…”
Section: Higher-order Thinking Assessment Methodsmentioning
confidence: 99%
“…This study refers to this traditional concept mapping as scratch concept map composition (SC-Mapping). Prior studies have shown SC-Mapping could develop HOT of students [10]- [13]. Meanwhile, the concept map recomposition (KB-mapping)constructing the concept map from the given kit containing concepts and links-has been proven to attain similar or more learning achievements than SC-Mapping [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is a significant relationship between the ability to create concept maps and learning outcomes (Carr-Lopez et al, 2014;Maurisa & Herkules, 2016). Furthermore, learning via concept maps can help independent learning, improve critical thinking skills, analysis, and support interest in learning (Biniecki & Conceição, 2016;Jamaludin, 2017;Maryam et al, 2021).…”
Section: Concept Map Typesmentioning
confidence: 99%